Preparation and characterization of a GSH-responsive drug-loaded polymer nanoparticle/silk fibroin composite hydrogel - Li, Yanjiu; Li, Rong (Frontiers in Bioengineering and Biotechnology, 2025)
This study addressed the poor water solubility and low bioavailability of curcumin (CUR), along with the inadequate stability of existing nano-delivery systems. A composite delivery system (GEL-PNES-CUR) combining a glutathione (GSH)-responsive drug-loaded polymeric nanoparticle (NP@PNES-CUR) with a silk fibroin hydrogel (SF-GEL) was constructed. Firstly, SF-GEL was prepared using the HRP/H2O2 system. A three-dimensional porous network structure was imparted to SF-GEL through enzymatic cross-linking. SF-GEL exhibited injectability, making it suitable for minimally invasive therapy, combined with a high swelling ratio (546%) and excellent rheological properties (storage modulus G′ reaching 10,000 Pa). Secondly, a GSH-sensitive polymer (PNES) was designed and synthesized. Rigid bipyridyl groups were introduced into the PNES backbone to enhance π-π stacking interactions. Subsequently, PNES was combined with CUR to prepare NP@PNES-CUR.For NP@PNES-CUR, an encapsulation efficiency of 47.7% for CUR was achieved (compared to only 7.5% for the control group). The GSH-responsive characteristics of disulfide bonds were utilized to achieve CUR release triggered by the inflammatory microenvironment (a release rate of 79.8% was reached within 24 h). Finally, NP@PNES-CUR was loaded into SF-GEL to prepare GEL-PNES-CUR. GEL-PNES-CUR was demonstrated to possess the function of sustained CUR release. Cell experiments indicated that GEL-PNES-CUR possessed good biocompatibility (cell viability >70%). This study provides a novel material for complex inflammation treatment, combining mechanical adaptability with controllable drug release functionality.